Joint observation in NICU (JOIN): study protocol of a clinical randomised controlled trial examining an early intervention during preterm care. Issue 3 (30th March 2019) - Schneider, Juliane; Borghini, Ayala; Morisod Harari, Mathilde; Faure, Noemie; Tenthorey, Chloé; Le Berre, Aurélie; Tolsa, Jean-François; Horsch, Antje
Abstract : Introduction: Preterm birth may generate significant distress among the parents, who often present with difficulties in appropriating their parental role. Parental stress and low perceived parental self-efficacy may interfere with the infant's socioemotional and cognitive development, particularly through disrupted parent–infant interactions. Perceived parental self-efficacy represents the belief of efficacy in caring for one's own infant and successful incarnation of the parental role, as well as the perception of one's own abilities to complete a specified task. Interventions to support parental role, as well as infant development, are needed, and parental self-efficacy represents a useful indicator to measure the effects of such early interventions. Methods and analysis: This study protocol describes a randomised controlled trial that will test an early intervention in the neonatal intensive care unit (NICU) (JOIN: Joint Observation In Neonatology) carried out by an interdisciplinary staff team. Mothers of preterm neonates born between 28 and 32 6/7 weeks of gestational age are eligible for the study. The intervention consists of a videotaped observation by a clinical child psychologist or child psychiatrist and a study nurse of a period of care delivered to the neonate by the mother and a NICU nurse. The care procedure is followed by an interactive video guidance intended to demonstrate the neonate's abilities and resources to his parents. The primary outcome will be the difference in the perceived maternal self-efficacy between the intervention and control groups assessed by self-report questionnaires. Secondary outcomes will be maternal mental health, the perception of the parent– infant relationship, maternal responsiveness and the neurodevelopment of the infant at 6 months corrected age. Ethics and dissemination: Ethical approval was granted by the Human Research Ethics Committee of the Canton de Vaud (study number 496/12). Results from this study will be disseminated at national and international conferences, and in peer-reviewed journals. Trial registration number: NCT02736136, Pre-results.